Administrative and financial corruption in Egypt in the era of the Maritime Mamluk state - Ali, Abdul Khaleq Khamis (Al-Adab Journal, 2015)
This paper, which deals with the financial and administrative corruption in Egypt during the Naval Mamluks state , concludes the following : - Bribe and corruption were known for the highest authority in the Naval Mamluks state , that is , the Sultan . Studies reveal that some were involved in receiving money for nominating a minister or a judge or else. This is basically dangerous because , traditionally, that who fights corruption , faces it and punishes those who do it is the Sultan himself. And how the case is when the Sultan is corrupted. The consequence is horrible because it casts its bad impacts and shadows on every part of life . - Bribe became widespread for that who is in-charge of administrative and financial jobs, or the so-called ’ official jobs ’ , whether through spending large sum of money to get the post , or through justifying the money taken in different ways from those who work for them ,i.e., through doing their own jobs . This made an increase in corruption widely because it led to compete over posts and jobs. Thus , jobs were being given for those who paid more money , and in turn , they tried to indemnify the money spent for taking the post by doing their job and taking money no matter whether legally or not. - The Mamluke Sultanate encouraged corruption indirectly through paying no attention to those who are corrupted , and when the Sultanate wanted to set the corrupted aside which was regarded very easy because there were files and documents which condemn the corrupted in addition to seize all their properties which were taken over by bribe then in turn became the property of the Sultanate that was the only beneficiary. - Bribe and corruption reached to the court , the important religious and administrative institution , which is the basis of justice and that which protects those who are oppressed and victims of justice. This brought about breaking down the real lawful judgments and thus, judges sentenced the bribed and corrupted influenced by the personal interest . - The Mamluke military institution witnessed corruption in some of its posts and jobs and this traditionally made this important institution which , is regarded the basic factor for states and kingdoms, to be weak. As a result of this , the state became weaker against the weakest internal threat beside the outer ones.